The South China Sea disputes past, present, and future - Roy, Nalanda (Lexington Books, 2016)
This study provides political and economic analyses of current controversies in the South China Sea. It examines enduring territorial disputes, competing maritime claims, and the historical roots of regional mistrust. It also analyzes how such antagonisms affect the regional security structure and offers solutions to resolve the conflicts.